Estudo numérico do impacto das emissões veiculares e fixas da cidade de Manaus nas concentrações de poluentes atmosféricos da região amazônica - Rafee, Sameh Adib Abou (2015)
The main aim of this study was to evaluate the impact of the urban pollution plume from the city of Manaus by emissions from mobile and stationary sources in the atmospheric pollutants concentrations of the Amazon region, by using The Weather Research and Forecasting with Chemistry (WRF-Chem) model. The air pollutants analyzed were CO, NOx, SO2, O3, PM2.5, PM10 and VOCs. The model simulations have been configured with a grid spacing of 3 km, with 190 x and 136 y grid points in horizontal spacing, centered in the city of Manaus during the period of 17 and 18 of March 2014. The anthropogenic emissions inventories have gathered from mobile sources that were estimated the emissions of light and heavy-duty vehicles classes. In addition, the stationary sources have considered the thermal power plants by the type of energy sources used in the region as well as the emissions from the refinery located in Manaus. Various scenarios have been defined with numerical experiments that considered only emissions by biogenic, mobile and stationary sources, and replacement fuel from thermal power plant, along with a future scenario consisting with twice as much anthropogenic emissions. A qualitative assessment of simulation with base scenario has also been carried out, which represents the conditions of the region in its current state, where several statistical methods were used in order to compare the results of air pollutants and meteorological fields with observed ground-based data located in various points in the study grid. The qualitative analysis showed that the model represents satisfactorily the variables analyzed from the point of view of the adopted parameters. Regarding the simulations, defined from the base scenarios, the numerical experiments indicate relevant results such as: it was found that the stationary sources scenario, where the thermal power plants are predominant, resulted in the highest concentrations, for all air pollutants evaluated, except for carbon monoxide when compared to the vehicle emissions scenario; The replacement of the energy matrix of current thermal power plants for natural gas have showed significant reductions in pollutants analyzed, for instance, 63% reductions of NOx in the contribution of average concentration in the study grid; A significant increase in the concentrations of chemical species was observed in a futuristic scenario, reaching up to a 81% increase in peak concentrations of SO2 in the study area. The spatial distributions of the scenarios have showed that the air pollution plume from Manaus is predominantly west and southwest, where it can reach hundreds of kilometers to areas dominated by original soil covering.